2018
DOI: 10.1186/s12913-018-2963-7
|View full text |Cite
|
Sign up to set email alerts
|

Substance use and self-harm: a cross-sectional study of the prevalence, correlates and patterns of medical service utilisation among patients admitted to a South African hospital

Abstract: BackgroundSubstance use is a potentially modifiable risk factor for suicidal behaviour. Little is known about the epidemiology of substance use among self-harm patients in South Africa. This study set out to collect epidemiological data about the prevalence, correlates, and patterns of medical service utilisation among self-harm patients who used substances at the time of self-injury.MethodsData from 238 consecutive self-harm patients treated at an urban hospital in South Africa were analysed using bivariate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 32 publications
0
5
2
Order By: Relevance
“…The larger project is a joint study between the Department of Psychology at Stellenbosch University and the Department of Psychiatry and Mental Health at the University of Cape Town and has resulted in publications describing the methods of self-harm 25 and associations between DSH and substance use. 26 The data we present here have, however, not been previously reported.…”
Section: Methodscontrasting
confidence: 58%
See 1 more Smart Citation
“…The larger project is a joint study between the Department of Psychology at Stellenbosch University and the Department of Psychiatry and Mental Health at the University of Cape Town and has resulted in publications describing the methods of self-harm 25 and associations between DSH and substance use. 26 The data we present here have, however, not been previously reported.…”
Section: Methodscontrasting
confidence: 58%
“…25 and associations between DSH and substance use. 26 The data we present here have, however, not been previously reported.…”
Section: Study Design Setting and Samplingcontrasting
confidence: 58%
“…However, Breet et al, [26] reported that selfinjury not to die was significantly related to acute use of substances, while Suicidal to die was insignificantly related to acute use of substances. This study's association between anxiety and depression can be explained by the direct causation model, according to which one condition causes or lowers the threshold for the manifestation of the other disorder [27].…”
Section: Discussionmentioning
confidence: 97%
“…Failure to identify the risk has potential consequences for the overall health outcomes. 16 Screening for substance abuse can improve health outcomes, and universal screening may be justifiable in high-prevalence health settings. 17 Self-report screening tools accurately identify substance abuse and are commonly implemented by PHC providers.…”
Section: Screeningmentioning
confidence: 99%